Irrigation, collective action, and property rights - Vermillion, Douglas L. (International Food Policy Research Institute, 2004)
Governments are now shifting their role from direct management of irrigation systems to regulation of the water sector, provision of support services to water user associations, and capacity building among water user associations and irrigation service providers.... International experience suggests that successful irrigation sector reform programs establish both a policy working group and a national secretariat that help to guide and coordinate the planning and implementation of the reform process. The process should include: strategic, participatory planning; research and stakeholder consultations; mobilization of political support; design and adoption of an appropriate policy, legal, institutional, and regulatory framework; strategy to coordinate lending and technical assistance; public awareness campaigns; and monitoring, evaluations, and course corrections. -- from Text.